Analisis Struktur Industri Unggulan Pada Pembangunan Negara - Tina Safira; Mohamat Masrur Mauridhoh; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Leading industries play an important role in a country’s economic development. The comparative and competitive advantages of this industry produce production output, employment opportunities and a domino effect that benefits other sectors. This research aims to analyze the structure f leading industries and identify the factors driving and inhibiting their growth. The benefits of research are also felt by policy makers and practitioners in formulating industrial growth strategies, as well as by academics and researchers in enriching theoretical studies of economic and industrial development